Deformation Mechanism and Control of the Surrounding Rock during Gob-Side Entry Driving along Deeply Fully Mechanized Caving Island Working Face - Fei Liu; Yongsheng Han (Geofluids)
The deformation control of the surrounding rock during gob-side entry driving along deeply fully mechanized caving island working face is one of the main bottlenecks affecting the successful and efficient production in modern mining. The prior ordinary fully mechanized caving theories have been difficult in ensuring the safe and efficient mining along island working face during gob-side entry driving under the complex conditions in the west. Therefore, it is of great theoretical and practical significance to carry out the research on the deformation mechanism and control of the surrounding rock during gob-side entry driving along deeply fully mechanized caving island working face. This paper, by means of experimental research, theoretical analysis, numerical calculation, and field industrial test, systemically researched the deformation characteristics of the surrounding rock and the law of strata behaviors during gob-side entry driving along deeply fully mechanized caving island working face.